Corporate Social Responsibility, Enterprise Risk Management, Nilai Perusahaan, dan Kinerja Keuangan sebagai Pemoderasi - Marthadevi, Ni Made Maswita; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2023)
Globalization causes competition between companies to become tighter so that companies compete so that their existence remains well recognized by the market. High company value can improve welfare and become a consideration for shareholders. This research aims to prove the effect of disclosure of corporate social responsibility and enterprise risk management on company value with financial performance as a moderator. The research population is Investor Index 33 issuers on the Indonesia Stock Exchange for the period 2018-2020. The sample was selected using a purposive sampling method, a sample of 22 issuers was obtained, with 66 data observations over three years. Six outlier data were excluded, so only 60 data were used. The data analysis technique is Moderated Regression Analysis (MRA). The results of the analysis show that corporate social responsibility disclosure has a negative influence on company value, enterprise risk management has a positive effect on company value, and financial performance weakens the influence of corporate social responsibility disclosure and enterprise risk management on company value. Keywords: Corporate Social Responsibility; Enterprise Risk Management; Financial Performance; Company Value.